The Getty Fiend - White, Ken (punctum books, 2024)
The Getty Fiend, a contemporary medieval melodrama set in Los Angeles's Getty Museum, takes the reader on a tour filled with rock stars and warrior-kings, werewolves and archivists, sartorial Huns and libertine saints, all seen through the keenly dramatic flair of a collector's eye. A cinematic and labyrinthine take on pulp horror, Ken White's screenplay-in-verse is a monster mash-up of forms and languages, facades and carnal catastrophes, archaic languages and misplaced rhetorics-a campy, fantastical gender-bending transformation into the inadvertently divine.